Promoting Student Wellness and Self-Care During COVID 19: The Role of Institutional Wellness - Vazquez Morgan, Marie (Frontiers in Psychiatry, 2021)
Stress and burnout are serious and growing threats to the mental health of medical trainees. Recent estimates of burnout in medical students and residents are quite high, with more than half displaying signs of stress, anxiety, and depression. The COVID-19 pandemic has only heightened the state of poor mental health in these student populations. It is the position of LSU Health Shreveport Office of Institutional Wellness that a critical need exists for academic institutions to evaluate challenges to self-care and wellbeing in medical trainees. Such evaluations may pave the way for the development of effective institutional wellness initiatives and strategies, to reduce barriers to self-care to promote better mental and physical health and facilitate improved quality of life in medical students and residents.